Experience psychology - King, Laura A. (McGraw-Hill, 2013)
Experience Psychology is a complete learning system that empowers students to personally, critically, and actively experience the impact of psychology in everyday life. Experience Psychology is about, well, experience—our own behaviors; our relationships at home and in our communities, in school and at work; and our interactions in different learning environments. Grounded in meaningful real-world contexts, Experience Psychology’s contemporary examples, personalized author notes, and applied exercises speak directly to students, allowing them to engage with psychology and to learn verbally, visually, and experientially—by reading, seeing, and doing. With the Experience Psychology learning system, students do not just “take” psychology but actively experience it